IMPLEMENTASI INFORMATION RETRIEVAL DALAM PEMBUATAN APLIKASI PIANO COMPOSER MENGGUNAKAN JAVA APPLET - Marinata Vanny Tarida Sitohang; Anton Setiawan Honggowibowo; Dwi Nugraheny (Compiler, 2012)
Music is an integral part in human life nowadays. Musical instruments that is being used commonly by the musician is piano. The piano is used because of its widest range of musical notes compared to other musical instruments, and those enable musician to compose musical notes with a piano. In general, there is one obstacle that prevents musician to have a piano, and that is the expensive price of a piano.On this Final Assignment, there is a java based piano composer applet that runs on the web platform to provide an easier way to play a piano and music composition online. With this application, the user only need to compose the musical score, then the application itself will process it into a MIDI formatted file.Based on the survey held with some musicians, can be concluded that the piano composer application can be used by the user to play piano and to compose musical notes very well.